2012
DOI: 10.4253/wjge.v4.i2.28
|View full text |Cite
|
Sign up to set email alerts
|

Single balloon enteroscopy: Technical aspects and clinical applications

Abstract: The small bowel has long been considered a black box for endoscopists because of its long length and the presence of multiple complex loop. Most of the small bowel is inaccessible by traditional endoscopic means. In addition, radiographic studies have significant limitations with regard to diagnostic yield, and surgery is an invasive alternative. This limitation was overcome through the development of balloon enteroscopy that becomes established throughout the world for diagnostic and therapeutic examinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Although intraoperative enteroscopy has been shown to avoid multiple enterotomies and reduce the risk of short bowel syndrome, disadvantages included high complication rate, and many patients required multiple laparotomies because of the growth of existing polyps and/or the appearance of new lesions (24,25). The introduction of balloon-assisted enteroscopy into clinical practice has allowed the visualization of the entire small bowel, enabling the management of unreachable lesions by standard endoscopic means (21,22). Studies in adults have shown that DBE is useful for treating small bowel polyps in patients with PJS (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although intraoperative enteroscopy has been shown to avoid multiple enterotomies and reduce the risk of short bowel syndrome, disadvantages included high complication rate, and many patients required multiple laparotomies because of the growth of existing polyps and/or the appearance of new lesions (24,25). The introduction of balloon-assisted enteroscopy into clinical practice has allowed the visualization of the entire small bowel, enabling the management of unreachable lesions by standard endoscopic means (21,22). Studies in adults have shown that DBE is useful for treating small bowel polyps in patients with PJS (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…For both anterograde and retrograde approaches, standard advancement techniques have been used (21,22). The enteroscope has a working length of 200 cm with an outer diameter of 9.2 mm and an operative channel size of 2.8 mm.…”
Section: Single-balloon Enteroscopymentioning
confidence: 99%
“…14 Single-balloon enteroscopy developed subsequently is easier to perform, requires a shorter learning curve, and is a less complex procedure than DBE. [18][19][20][21] Spiral enteroscopy is easier to perform and is faster than its predecessors. 22,23 One of the major advantages of spiral enteroscopy is the rapid advancement and stable controlled withdrawal facilitating efficient therapeutic intervention.…”
Section: Diagnosis Of Stricturesmentioning
confidence: 98%
“…Esophagus Barrett's Esophagus [17] E>S Esophageal Varices [18] E>S Gastrointestinal Foreign Bodies [19] E>S Benign Esophageal Strictures [20] E>S Palliation of Malignant Esophageal Strictures [21] E>S Zenker's Diverticulum [22] E>/=S Postoperative Upper Gastrointestinal Leaks [23] E>S GERD [24] E<S Achalasia Cardia [25] E>/=S Stomach Peptic Ulcer Bleeding [26] E>S Gastric Varices [27] E>S Portal Hypertensive Gastropathy [28] E>S Pyloric Stenosis-Benign [29] E<S Palliation of Pyloric Stenosis-Malignant [30] E>S Early Gastric Cancer and Gastric Tumors [31] E>S Obesity [32] E</=S Small Intestine Small Bowel bleeding [33] E>S Small Bowel Polyps [33] E<S Biliary Common Bile Duct Stone [34] E >/=S Benign Biliary Strictures [35] E</=S Palliation of Malignant Biliary Strictures [36] E>S Biliary Complications after Liver Transplantation [37] E>S Pancreas…”
Section: Organ Disease Condition Role Of Endoscopy(e) Vs Surgery(s)mentioning
confidence: 99%